The Effect of Discussion Strategy to Improve Students’ Speaking Fluency In the XI class of Ashabul Yamin Boarding School - Wat Yurismawati; Hilma Pami Putri; Loli Safitri; Irwandi Irwandi (Pusat Riset dan Inovasi Nasional, 2023)
The study was carried out in response to a number of issues that were discovered in the field. There were issues with fluency among the students. When speaking in front of the class, the pupils appeared nervous because they lacked confidence in their ability to communicate their views in English. They were frightened of making grammatical, pronunciation, or fluency errors. The researcher employed a conversation method to help students improve their speaking fluency in this study. The methodology of this research was quantitative research, and the type of research was experimental research. This study used a pre-experimental design using a one-group pretest-posttest design. The participants in this study were all of the students of Ashabul Yamin Boarding School's grade XI B. The researcher employed the purposive sampling technique to collect the sample, with 16 students from XI B class serving as the study's sample. In other words, the Ha was accepted, which said that adopting discussion approach to improve students' speaking fluency in the XI class of Ashabul Yamin Boarding School had a substantial effect. It may be stated that employing the Discussion Strategy aided students in learning to communicate, particularly in speaking fluency.